The safe library : keeping users, staff, and collections secure - Albrecht, Steve, 1963- (Rowman & Littlefield, 2023)
"This book provides advice and support to help library employees best deal with sexually harassing patrons, unruly groups of students, gang members, thieves, Internet hogs, and others who can disrupt the safe library environment"--